Trajectories of Overweight and their Association with Adolescent Depressive Symptoms - Martin-Storey, Alexa (Health Psychol, 2015)
OBJECTIVE: To explore the potential for a developmental approach to reveal new insights into the well-documented link between weight and depressive symptoms. METHODS: Latent class analysis identified multiple trajectories of overweight from 24 months to 15 years in the NICHD Study of Early Child Care and Youth Development (n = 957). Structural equation models then used these classes to predict depressive symptoms at age 15. RESULTS: Five latent classes captured continuity and change in weight from early childhood into middle adolescence. Controlling for current weight, stably overweight girls tended to have the most depressive symptoms, but popularity and positive image appeared to buffer against some of the risks that girls faced from being stably overweight or becoming overweight in early to middle childhood. Notably, boys’ longitudinal weight patterns were not associated with their depressive symptoms in adolescence. CONCLUSIONS: Weight histories, controlling for current weight, are important for understanding the psychological experience of overweight, especially when such histories are considered in relation to other aspects of psychosocial functioning.